2008
DOI: 10.1111/j.1572-0241.2007.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antibiotics Cannot Reduce Infected Pancreatic Necrosis and Mortality in Acute Necrotizing Pancreatitis: Evidence From a Meta-Analysis of Randomized Controlled Trials

Abstract: Prophylactic antibiotics cannot reduce infected pancreatic necrosis and mortality in patients with ANP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 24 publications
1
74
0
4
Order By: Relevance
“…Subsequent subgroup analysis confirmed that antibiotics were not significantly superior to placebo or no treatment in reducing the rate of infected necrosis or mortality. 73 A 2012 meta-analysis of 11 RCTs looking at the efficacy of prophylactic antibiotics in acute pancreatitis calculated the number needed to treat to be 1429, 74 and yet another meta-analysis of 14 RCTs (n = 841) showed no statistically significant reduction in mortality (RR 0.74, 95% CI 0.50-1.07), incidence of infected pancreatic necrosis (RR 0.78, 95% CI 0.60-1.02), incidence of nonpancreatic infections (RR 0.70, 95% CI 0.46-1.06), or in surgical interventions (RR 0.93, 95% CI 0.72-1.20). 75 In light of the lack of demonstrated benefit of prophylactic antibiotics in the treatment of acute pancreatitis, the adverse effects of this practice must be carefully considered.…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%
“…Subsequent subgroup analysis confirmed that antibiotics were not significantly superior to placebo or no treatment in reducing the rate of infected necrosis or mortality. 73 A 2012 meta-analysis of 11 RCTs looking at the efficacy of prophylactic antibiotics in acute pancreatitis calculated the number needed to treat to be 1429, 74 and yet another meta-analysis of 14 RCTs (n = 841) showed no statistically significant reduction in mortality (RR 0.74, 95% CI 0.50-1.07), incidence of infected pancreatic necrosis (RR 0.78, 95% CI 0.60-1.02), incidence of nonpancreatic infections (RR 0.70, 95% CI 0.46-1.06), or in surgical interventions (RR 0.93, 95% CI 0.72-1.20). 75 In light of the lack of demonstrated benefit of prophylactic antibiotics in the treatment of acute pancreatitis, the adverse effects of this practice must be carefully considered.…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%
“…As mentioned above, 6 of the 18 studies included in the current review were associated with reduced mortality when prophylactic antibiotics were used and the remaining 12 meta-analyses did not recommend the use of prophylactic antibiotic as there was no significant reduction in mortality with them. [25][26][27][30][31][32][33][34][35][36][37][38] These meta-analyses used a combined total of 14 RCTs with total study population varied from 329 to 841 patients.…”
Section: Mortality In Pancreatitis: Are Antibiotics Protective?mentioning
confidence: 99%
“…Antibiotic prophylaxis to reduce infective complications in acute pancreatitis was evaluated in a series of randomized trials [4][5][6][7][8][9][10][11][12]. However meta-analyses of these trials do not support antibiotic prophylaxis in acute pancreatitis [13][14][15]. Summarising this evidence, the International Association of Pancreatology/American Pancreatic Association (IAP/APA) produced evidence-based guidelines in 2013 for the management of acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%